Applications of Cross-Adaptive Audio Effects: Automatic Mixing, Live Performance and Everything in Between - Reiss, Joshua D.; Brandtsegg, Øyvind (Frontiers in Digital Humanities, 2018)
This paper provides a systematic review of cross-adaptive audio effects and their applications. These effects extend the boundaries of traditional audio effects by potentially having many inputs and outputs, and deriving their behaviour based on analysis of the signals. This mode of control allows the effects to adapt to different material, seemingly ``being aware'' of what they do to signals. By extension, cross-adaptive processes are designed to take into account features of, and relations between, several simultaneous signals. Thus a more global awareness and responsivity can be achieved in the processing system. When such a system is used in real-time for music performance, we observe cross-adaptive performative effects. When a musician uses the signals of other performers directly to inform the timbral character of her own instrument, it enables a radical expansion of the human-to-human interaction during music making. In order to give the signal interactions a sturdy frame of reference, we engage in a brief history of applications as well as a classification of effects types and clarifications in relation to earlier literature. With this background, the current paper defines the field, lays a formal framework, explores technical aspects and applications, and considers the future of this growing field.